Sex Education as an Effort to Prevent Sexual Violence Against Children - Sumiyati, Sumiyati (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
Child is a mandate given by God as a surrogate. The mandate received by each parent will be asked about the responsibility someday. Parents certainly hope their children will be success in their life. Some case of sexual violence in children of course led to a deep concern for parents. How crime and sexual violence can happen to an innocent children. One of the efforts to prevent sexual violence against children is through giving sex education. Sex education provide children about how he understands sex, keep their self and limbs, and how to train children to be able to communicate effectively with parents. Hopefully, by the sex education, children can build a positive attitude and behaviour, also they have a good confidence to ask information to parents and the significant others about all of the things that they wanted to know, include something like why some organ in men and women are different. If the sex education for early childhood is successful, then the opportunity for children to enjoy the future will be more wide open, without overshadowed by the fear of child predators who will take away their future. Keywords: sex education, sexual violence, early childhood. Anak merupakan amanah yang diberikan oleh Allah sebagai titipan. Amanah yang diterima oleh setiap orangtua tentu saja akan dimintakan pertanggungjawabannya kelak. Orangtua tentu berharap kesuksesan dan keberkahan bagi putra putrinya. Terjadinya tindak kekerasan seksual pada anak tentu saja membuahkan keprihatinan yang mendalam bagi orangtua. Bagaimana kejahatan dan kekerasan seksual ini dapat menimpa anak usia dini yang tidak berdosa. Salah satu upaya untuk mencegah terjadinya kekerasan seksual pada anak ini adalah melalui sex education atau pendidikan seks untuk anak. Sex education membekali anak tentang bagaimana dia memahami jenis kelaminnya, menjaga diri dan anggota badannya, serta bagaimana melatih anak untuk dapat berkomunikasi yang efektif dengan orangtua. Diharapkan dengan adanya sex education ini anak mampu untuk selalu bersikap positif dan memiliki kepercayaan diri yang tinggi untuk bertanya dan mencari informasi kepada orangtua dan orang terdekat tentang segala hal yang ingin diketahuinya, termasuk tentang organ tubuh, kenapa laki-laki berbeda dengan perempuan. Apabila pendidikan seks untuk anak usia dini ini berhasil, maka kesempatan atau peluang anak untuk menikmati masa depannya akan semakin terbuka lebar, tanpa dibayang-bayangi oleh ketakutan akan adanya predator anak yang akan merenggut masa depan mereka. Kata kunci: sex education, kekerasan seksual, anak usia dini.